2021
DOI: 10.1002/lsm.23402
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Non‐Ablative Resurfacing of Soft Tissues by Repetitive Er:YAG Laser Pulse Irradiation

Abstract: Background and Objectives Recently, several minimally invasive gynecological, ENT and esthetic procedures have been introduced that are based on delivering “smooth” sequences of Er:YAG laser pulses to cutaneous or mucosal tissue at moderate cumulative fluences that are not only below the ablation threshold but typically also do not require local anesthesia.  To explain the observed clinical results using “smooth‐resurfacing,” it has been suggested that in addition to the direct heat injury to deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 69 publications
0
29
0
Order By: Relevance
“…These fast shocks initiate the wound healing process, as tissue cells recognize them as wounds producing ones, although - being short enough, they do not produce any injuries. Effects of such wound healing process were detected even 2 mm deep in the mucosa [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These fast shocks initiate the wound healing process, as tissue cells recognize them as wounds producing ones, although - being short enough, they do not produce any injuries. Effects of such wound healing process were detected even 2 mm deep in the mucosa [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of tissue damage dynamics have shown that when considering extremely short and long exposure times, cell viability cannot be described by a single biochemical process of Equation (1). 26 At extremely short exposure times (commonly present during Er:YAG laser treatments), 18,[27][28][29] the critical temperature exhibits a shift to temperatures, which are much higher than what would be expected from a single biochemical process characterizing the damage dynamics at long exposure times. 25 In this study, the variable heat shock (VHS) tissue response model will be applied, 26 which takes into account the observed deviation by describing the cell viability as a combined effect of two biochemical processes that dominate cell survival characteristics at very short and very long exposure times (see Figure 1).…”
Section: Analytical Modelmentioning
confidence: 99%
“…Pulsed mid-infrared Er:YAG laser is by now an accepted tool for performing ablative [1][2][3] as well as nonablative medical procedures. [4][5][6][7][8] This is because the Er:YAG laser wavelength (λ = 2.94 μm) coincides with the major absorption peak of the water molecule, and is thus highly absorbed in virtually all biological tissues. 9,10 There are three basic phases in tissue heating upon exposure to Er:YAG laser irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations